Awareness about breast cancer among women aged 15 years and above in urban slums: a cross sectional study - Katkuri, Sushma; Gorantla, Misha (International Journal Of Community Medicine And Public Health, 2018)
Background: Breast cancer is the second most common cancer overall and is the most common cancer in women worldwide, both in the developed and developing countries. There are about 1.38 million new cases and 458,000 deaths from breast cancer each year. The aims and objectives of the study were to determine the awareness about breast cancer among urban slum women. Methods: A community based cross–sectional study was conducted at urban slum Shahpur Nagar, Hyderabad. The study participants were above 15 years of age and the study was conducted for a period of one month. A total of 200 study participants were enrolled. Results: Only 35% of the study population was aware about the early danger signs and 66% were unaware. Those who were aware in that 46.3% were breast lump is the early warning sign of breast cancer, followed by 28% said breast abscess, 16% pain in breast, 9% painless lump and 1.4% said for nipple discharge. Regarding skin changes nobody was aware about it. Awareness about risk factors for breast cancer was very poor that is only 21% were knowing about the risk factors about breast cancer. Near about 54% said they are aware about breast cancer by clinical examination done by doctor, 35% said by self breast examination and 12% said by mammography. Conclusions: Intensified health education campaigns should be conducted in the community and they be made aware about breast cancer.